Trends in Scientific Attitude Research in Science Education, 2016–2025: A Bibliometric Analysis and Systematic Literature Review - Ahmad Aris Arifin; Agus Ramdani; A. Wahab Jufri; Satutik Rahayu (Lembaga Bale Literasi, 2026)
This study aims to analyze research trends on scientific attitude in science education during 2016–2025 by combining bibliometric analysis and a systematic literature review (SLR). The bibliometric data were retrieved from the Dimensions database. The search was conducted using the keyword “scientific attitude research in science education” within the 2016–2025 publication range. In the initial stage, the search using the full data option yielded 1,257,505 documents under the publications category. To improve the relevance of the dataset to the focus of the study, the search was then restricted to the occurrence of the keyword in the title and abstract fields, reducing the dataset to 2,679 publications, which were then exported for bibliometric analysis. The data were analyzed using VOSviewer, while the SLR of 27 selected articles was conducted to identify major themes, methodological approaches, research contexts, and key findings. The results indicate a significant increase in publications on scientific attitude over the past decade. Bibliometric mapping highlights learning, teachers, culture, community, and effectiveness as central themes in the research network. The SLR findings show that scientific attitude is commonly developed through inquiry-based learning, contextual learning experiences, and the integration of local culture into science education. However, studies that explicitly integrate ethnoscience reconstruction into instructional tools to foster scientific attitude remain limited. Therefore, this study emphasizes the importance of developing contextual, culture-based, and ethnoscience-oriented science learning to strengthen scientific attitude.